D27 Neuroinflammation and changes in serotonin metabolism in presymptomatic HD gene carriers: a dual tracer positron emission tomography (PET) study. (13th September 2016) - Trender-Gerhard, Iris; McDonald, Kathryn; Talbot, Peter; Craufurd, David; Gerhard, Alex
Abstract : Background: Huntington's disease (HD) is a neurodegenerative disease clinically characterised by progressive movement disorders, neuropsychiatric disturbances and cognitive impairment. Genetic testing enables us to investigate early changes in presymptomatic individuals carrying the abnormally expanded trinucleotide (CAG) repeat length on chromosome 4, who have not yet developed the characteristic motor disturbances of the disorder. Affective symptoms (depression and anxiety), irritability and apathy are the core psychiatric problems in presymptomatic HD but the pathophysiological substrate of these features in HD is not well understood. There is emerging evidence that depression might be associated with peripheral and CNS inflammation. Of particular interest in this context is the role of activated microglia and their interaction with serotonin (5-HT) metabolism. Aims: To assess the correlation between microglial activation, serotonin receptor (SERT) binding and affective symptoms in presymptomatic HD gene carriers with in vivo PET imaging. Methods: 12 participants (male and female, age 18–60 years) with a positive predictive test for HD (CAG repeat length ≥36) who were found to show irritability or affective symptoms on the PBAs (Problem and Behaviour Assessment, short version) were recruited from the Genetic Medicine clinic at St Mary's Hospital, Manchester. Participants did not yet have a clinical diagnosis (based on motor symptoms) of HD. Participants underwent detailed clinical, neuropsychological and neuropsychiatric assessments in a cross-sectional design. [11C](R)-PK11195 PET (imaging microglial activation) and [11C]DASB-PET (measuring SERT binding) were obtained following standard protocols on the high resolution HRRT PET camera that allows evaluation of small brain structures (including brainstem nuclei) and structural MRI. Results: PET scanning has been concluded just before abstract submission, and the PK11195 and DASB PET are currently quantified. Regional binding potential (BP) values for both modalities are being correlated with clinical and affective parameters, and the results will be presented at the meeting. Funding: European Huntington's disease Network (EHDN), European Union's Seventh Framework Program (FP7/2007-2013) under grant agreement no. HEALTH-F2-2011–278850, (INMiND)